Næringarþekking meðal íslensks afreksíþróttafólks og þjálfara þeirra. Þróun og forprófun á spurningalista - Lilja Guðmundsdóttir 1990- (2019)
Diet plays a vital role in athletic performance and has to be adequate when it comes to the need for energy, macro- and micronutrients, fluids and timing of consumption. Research indicates that food intake of athletes often does not meet the dietary guidelines for this group. The reasons for inadequate dietary intake are multifactorial but seem partially affected by nutrition knowledge. Previous research has shown that nutrition knowledge among athletes is limited and little is known about the status in Iceland. The aim of this study was to assess the status of nutrition knowledge among Icelandic elite athletes and their coaches and to find and/or develop a convenient tool for Icelandic settings. Icelandic elite athletes (n=101) aged 19-38 years, 42 men and 59 women and their coaches (n=11) aged 24-56 years 8 men and 3 women, participated in the study. The study design was cross-sectional and assessed nutrition knowledge using questionnaires. In the collaboration of the Icelandic Sports and Olympic Federation and researchers an introduction letter and an electronic link to the questionnaires was distributed to the sports federations or directly to athletes, via e-mail. Total mean nutrition knowledge scores were 53.7 ± 12.6 among athletes and 63.2 ± 8.0 among coaches (p = .016). The total mean score of athletes in individual sport was higher than athletes in group sports (59.6 ± 9.4 vs. 50.5 ± 13.0, p = <.001). Ten of eleven coaches said they had advised their athletes on nutrition at some point. Athletes and coaches identified registered nutritionists/dietitians as their primary source of nutrition information and thereafter internet search. Nutrition knowledge could be better in both groups, especially among athletes. Sport federations and clubs should consider hiring a registered nutritionist/dietitian to ensure delivery of accurate information on sports nutrition. This would likely result in improved athletic performance. Mataræði spilar stórt hlutverk þegar kemur að frammistöðu í íþróttum og þarf að ...